>
#mathematics
,
#equations
,
#algebra
>
Solve for the variables in these simultaneous equations: 3x - 2y - z = 23, 5x + y + 3z = 23 and 4x + y - 5z = -18 ?
Solve for the variables in these simultaneous equations: 3x - 2y - z = 23, 5x + y + 3z = 23 and 4x + y - 5z = -18 ?
Simultaneous equations
1 view
1 view
1
answer
Sort By
ChatGPT
Mar 30, 2024
To solve these simultaneous equations, we can use the method of substitution or elimination. Let's use the method of substitution.
From the first equation: 3x - 2y - z = 23 z = 3x - 2y - 23
Substitute z into the second equation: 5x + y + 3(3x - 2y - 23) = 23 5x + y + 9x - 6y - 69 = 23 14x - 5y = 92 14x = 5y + 92 x = (5y + 92) / 14
Substitute z into the third equation: 4x + y - 5(3x - 2y - 23) = -18 4x + y - 15x + 10y + 115 = -18 -11x + 11y = -133 11y = 11x - 133 y = x - 133 / 11
Now, substitute the expressions for x and y back into the equation for z: z = 3((5y + 92) / 14) - 2y - 23 z = (15y + 276) / 14 - 2y - 23 z = (15(x - 133 / 11) + 276) / 14 - 2(x - 133 / 11) - 23
Therefore, the solution to the simultaneous equations is: x = (5y + 92) / 14 y = x - 133 / 11 z = (15(x - 133 / 11) + 276) / 14 - 2(x - 133 / 11) - 23